2020
DOI: 10.3390/insects11050290
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Sample Size for Population Genomic Study in a Global Invasive Lady Beetle, Harmonia Axyridis

Abstract: Finding optimal sample sizes is critical for the accurate estimation of genetic diversity of large invasive populations. Based on previous studies, we hypothesized that a minimal sample size of 3–8 individuals is sufficient to dissect the population architecture of the harlequin lady beetle, Harmonia axyridis, a biological control agent and an invasive alien species. Here, equipped with a type IIB endonuclease restriction site-associated (2b-RAD) DNA sequencing approach, we identified 13,766 and 13,929 single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 50 publications
(87 reference statements)
1
22
0
Order By: Relevance
“…In short, although large sample sizes are preferable for estimating genomic diversity and differentiation, coalescent modeling and estimation of evolutionary history can work well with smaller sample sizes and greater number of genomic loci. Using replicated random samples of 3000 SNPs (Single Nucleotide Polymorphisms) from a large 2bRAD dataset from populations of the biological control organism H. axyridis, Li et al, 2020 [122] determined that a minimum of 6 individuals per population are sufficient to accurately estimate within-and between-population genomic diversity and differentiation. The ideal sampling plan should also be informed by the sequencing platform or protocol used for genotyping-by-sequencing, which is optimized to run up to 96 uniquely barcoded individuals to obtain thousands of informative sites.…”
mentioning
confidence: 99%
“…In short, although large sample sizes are preferable for estimating genomic diversity and differentiation, coalescent modeling and estimation of evolutionary history can work well with smaller sample sizes and greater number of genomic loci. Using replicated random samples of 3000 SNPs (Single Nucleotide Polymorphisms) from a large 2bRAD dataset from populations of the biological control organism H. axyridis, Li et al, 2020 [122] determined that a minimum of 6 individuals per population are sufficient to accurately estimate within-and between-population genomic diversity and differentiation. The ideal sampling plan should also be informed by the sequencing platform or protocol used for genotyping-by-sequencing, which is optimized to run up to 96 uniquely barcoded individuals to obtain thousands of informative sites.…”
mentioning
confidence: 99%
“…The effects of sample size on population genetic diversity estimates have been investigated for different species (e.g., [4,9,11,[18][19][20]). The rationalization of the sampling effort is particularly important for research in the field of the population genetics of species of high conservation concern, such as European mink.…”
Section: Discussionmentioning
confidence: 99%
“…Different authors have suggested different numbers of randomly sampled individualsfrom four to six, in the case of high inter-population differentiation, to 20-30, for populations characterized by low or unknown levels of diversity or genetically depauperated, and even up to hundreds [1,8,[16][17][18][19][20]. Generally, it is claimed that large sample sizes or a large number of variable sites analyzed increases the accuracy of the estimation of genetic diversity parameters, but the rate of increase is not linear [10,19,21].…”
Section: Introductionmentioning
confidence: 99%
“…However, empirical studies have denoted that high throughput DNA sequencing have compensated smaller sample size with large number of generated SNP loci, to ensure high accuracy in estimating population genetic parameters [ 80 , 81 , 82 ]. Sample size as low as four individuals have been documented to be efficient in providing a precise estimate of FST values [ 83 , 84 ]. Indeed, a universal sample size rule may not be feasible to address the complexities in genomic kinship estimates [ 85 ].…”
Section: Discussionmentioning
confidence: 99%